Freshwater and Brackish Pre and Post-Reproductive Biological and Ecological Characteristics of the Sander lucioperca - Alieva, A; Bănăduc, D; Bakhshalizadeh , S; Nasibulina, B; Kurochkina, T; Popov, N; Linnik, A; Kuanysheva, G; Jussupbekova, N; Barbol, B; Ali, A (Journal of the Hellenic Veterinary Medical Society, 2025)
This research presents the results of study of the biological and ecological pre, post and reproduction characteristics of pike-perch (Sander lucioperca) in the Ponto-Caspian Basin, Dagestan area brackish and fresh waters. Samples were collected from Delta of the Terek River and the northwestern coast of the Caspian Sea, Dagestan. The reproductive biology was studied in two periods of life, in Dagestan sea waters and rivers through one year, 2019. Results state facts regarding age at first maturity, onset of spawning, fecundity, sex ratio, and the process of maturation of the reproductive organs. It was determined and found to be complementing each other for the populations of the two habitats. The pike-perch most important identified pre-reproductive, reproductive and post reproductive ethology characteristics are that after spawning in freshwater ecosystems, with its yearlings, migrates for foraging and sexual recovery and maturity to the sea to return then to the rivers of Dagestan for spawning again later. This specificity allows pike-perch both to use various ecosystems types trophic resources along its ontogeny, and keep a biological and ecological reproduction evolutionary potential in fresh, brackish and salty water ecosystems.